Pengaruh Employee Empowerment terhadap Employee Engagement Melalui Job Satisfaction pada Karyawan Corporate Secretary Bank Jatim - Rivanti Putri Kusuma Anwar (CV. ALIM'SPUBLISHING, 2026)
PT Bank Pembangunan Daerah Jawa Timur Tbk (“Bank Jatim”) is a regional-owned company engaged in banking. The main activity of this company is to collect and channel funds and provide other banking services to all customers in the East Java region. With the tagline